1990
DOI: 10.1088/0031-9155/35/3/006
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of absorbed doses near metal and dental material interfaces irradiated by X- and gamma-ray therapy beams

Abstract: Soft-tissue damage adjacent to dental restorations is a deleterious side effect of radiation therapy which is associated with low-energy electron scatter from dental materials of high electron density. This study was designed to investigate the enhancement of dose to soft tissue (or water) close to high electron-density materials and to measure the detailed lateral and depth-dose profiles in soft-tissue-simulating polymer adjacent to planar interfaces of several higher atomic-number materials: 18-carat gold de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 22 publications
1
44
0
4
Order By: Relevance
“…When a patient is treated with high atomic number metallic inhomogeneities embedded in body tissues, the dose at the metal-tissue interface increases significantly [9,10,30,33,35]. The metallic interfaces within the patient are formed by metallic prosthesis, metal tubes and pins placed after surgery, permanent metal implants, and the dental materials in teeth.…”
Section: Introductionmentioning
confidence: 99%
“…When a patient is treated with high atomic number metallic inhomogeneities embedded in body tissues, the dose at the metal-tissue interface increases significantly [9,10,30,33,35]. The metallic interfaces within the patient are formed by metallic prosthesis, metal tubes and pins placed after surgery, permanent metal implants, and the dental materials in teeth.…”
Section: Introductionmentioning
confidence: 99%
“…6 Other studies explain intuitive or anecdotal evidence of soft or hard tissue complications from radiation-dose enhancement proximal to metallic materials, such as gold dental crowns. 1,3,[7][8][9][10] Although the use of parallelopposed treatment fields minimizes these effects, the development of three-dimensional conformal techniques for treatment is reducing the prevalence of opposed fields, thus increasing the dose variances across interfaces between implants and normal tissue.…”
mentioning
confidence: 99%
“…A number of previous studies have revealed the need for more accurate dose calculation techniques, such as Monte Carlo algorithm, especially when the structure is very close to the metallic implants and the local dose gradient is high, for example the abutting buccal or lingual mucosa as being studied here 14, 15, 16. Novel dose distributions generated by varying beam intensity and geometry within the IMRT software may explain the discrepancy in the trend of dose perturbations between this study and previous studies17, 18 most of which were done based on conventional RT techniques.…”
Section: Discussionmentioning
confidence: 62%